Assailing "As": A Study of Wole Soyinka's Drama - Green, Jabulani Fraser Laurence (My University, 1989)
I must be honest and admit that I was only introduced to the name of Wole Soyinka in November 1986, in connection with his controversial Nobel acceptance speech at the Swedish Academy. For this reason, I have chosen to accurately represent my developing awareness with respect to this man and his writing, by viewing his work through the magnifying glass of that very political address, delivered three years ago. Since the germination of this study, I have discovered that I would not want to approach Soyinka ' s work from any other perspective than one that primarily considers the playwright's political analysis, his sense of social responsibility, and his commitment to human liberty and justice, as the foundations for an investigation of his plays.
The title of this thesis refers to a fictional philosophy of tyranny developed and attacked in Soyinka's powerful postCivil War play, Madmen and Specialists, but is relevant to the major themes explored in nearly everything the Nigerian has written, and is particularly central to the four plays examined here. Madmen and Specialists is considered, in this thesiS,in the second chapter, along with the later political farce, A Play of Giants, while the other two plays in the study, The Strong Breed and Death and the King's Horseman, are analysed in the first chapter, and linked by their tragic treatments of similar issues. Illuminated by the content of Soyinka's Nobel address which is discussed briefly in the opening chapter, this study aims to examine these plays which place the playwr'ight in his appropriate context as an African writer committed to the liberation of his people, his continent and the rest of humanity.
Keywords: English Language and Literature; English Language and Literature